1997
DOI: 10.1177/095632029700800408
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Human Immunodeficiency Virus Type 1 Reverse Transcriptase by Degradation Products of Ceftazidime

Abstract: SummaryPrevious work by Hafkemeyer et a/. (1991) [Nucleic Acids Research 19: [4059][4060][4061][4062][4063][4064][4065] indicated that a degradation product of ceftazidime, termed HP 0.35, was active against the RNase H activity of human immunodeficiency virus type 1 (HIV-1) and feline immunodeficiency virus (FIV) reverse transcriptase (RT) in vitro. Attempting to repeat these results, we isolated HP 0.35 from an aqueous degradation of ceftazidime and, after careful purification, we found HP 0.35 to be ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Since all the new dihedral angles in the pentamer structure showed a large variation, we put constraints on the torsions according to the tetramer distribution analysis. Fifteen rotatable bonds (1,4,5,7,9,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) were marked for exploration. Distribution analysis results from JMP revealed that most of the conformers had dihedral angle 18 near 87°, dihedral angle 19 near 74°, dihedral angle 20 near -48°, dihedral angle 21 near 157°, dihedral angle 22 near -85°, dihedral angle 24 near 84°, dihedral angle 25 near 4°, dihedral angle 26 near 143°, and dihedral angle 27 near 170° (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…Since all the new dihedral angles in the pentamer structure showed a large variation, we put constraints on the torsions according to the tetramer distribution analysis. Fifteen rotatable bonds (1,4,5,7,9,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) were marked for exploration. Distribution analysis results from JMP revealed that most of the conformers had dihedral angle 18 near 87°, dihedral angle 19 near 74°, dihedral angle 20 near -48°, dihedral angle 21 near 157°, dihedral angle 22 near -85°, dihedral angle 24 near 84°, dihedral angle 25 near 4°, dihedral angle 26 near 143°, and dihedral angle 27 near 170° (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…Purified HP 0.35 turned out to be labile and it tends to polymerize. It was proposed that low levels of polymerized material in the purified HP 0.35 have resulted in the reported activity (Baertschi et al, 1997). In contrast, the crude CDP effectively inhibited HIV-1 replication in acute cellular systems using cell lines, primary lymphocytes or macrophages infected with different HIV-1 isolates.…”
Section: Discussionmentioning
confidence: 99%
“…The polymer formed from HP 0.35 is polyanionic because of its derivation from ceftazidime. However, this feature of HMWP is most likely not a requirement for its activity because polymeric material formed from third-generation cephalosporins with no acidic functionality on the oxime also exhibit viricidal activity against HIV-1 [21,28].…”
Section: Introductionmentioning
confidence: 98%
“…The Lilly scientists showed that it was not the aldehyde degradation itself that had HIV activity, but rather a high molecular weight polymer (HMWP) formed from the aldehyde [21]. Subsequent work by the Swiss group in 2001 confirmed that it was a HMWP (MW 8000), not the aldehyde reported in 1991, that had a high inhibitory effect Our interest is in using molecular modeling to better understand the structure of the polymeric material containing 2-amino-4-thiazolyl-methoxyimino (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation